Phytochemical Analysis and Wound Healing Potential of Aloe vera (Aloe massawana) Peel Extract - Arcaya, Princess Jhazzy Panares; Capilitan, Laurianne Mae De Claro; Decano, Zhyanne Rejas; Dugaduga, Cathleen Denise Guyo; Hernane, Aldrich Glenn Lamasan; Calo, Jhovel Roy Dael; Saldo, Ian Jay Paspe (Asian Journal of Biological and Life Sciences, 2025)
Aim/Background: Aloe vera peel extract holds promise for wound healing, yet its specific phytochemical composition and therapeutic potential still need to be explored, especially in San Jose, Malaybalay City, Bukidnon. This study filled the gap by investigating the phytochemical constituents of Aloe vera (A. massawana) peel extract and its implications for wound healing. Materials and Methods: Aloe vera (A. massawana) peel samples were gathered from local residences using purposive sampling, transformed into ethanolic extracts, and then examined phytochemically. Several studies used color-based tests to determine the presence of anthraquinones, terpenoids, alkaloids, tannins, and flavonoids. Results: All five (5) trials on the assays of anthraquinones, flavonoids, and tannins yielded positive results from the phytochemical screening. The colors of these compounds were red, brown-yellow, and greenish-black, respectively. However, the findings of the five (5) alkaloids and terpenoids trial tests were dark green and black, indicating a negative observation. These findings suggest possible therapeutic advantages for wound healing. Conclusion: The study emphasized the importance of integrating innovative scientific methods with traditional medical understanding to improve healthcare procedures. Further research is necessary to fully understand the processes that underline Aloe vera's healing properties and maximize its therapeutic use in wound care.
Keywords: Aloe massawana; Aloe vera peel extract; Bioactive compounds; Phytochemical analysis; Wound healing